(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2017)
This paper investigates some of the main problems concerning the normativity of aesthetic judgments in Kant’s Critique of Judgment. Kant’s attempt to provide a transcendental foundation to aesthetic judgments clashes with the impossibility to find a determined conceptual rule under which they could be subsumed. This paper aims to discuss and clarify the set of problems derived from this attempt, focusing especially on the artistic perspective. In order to do that, it will be necessary to deal with the following notions: eautonomy, sensus communis aestheticus and genius. From this analysis it will emerge the importance of exemplarity as concept that allow us to highlight some implicit and usually neglected aspects of Kant’s aesthetic theory.